2021
DOI: 10.1119/5.0019668
|View full text |Cite
|
Sign up to set email alerts
|

Smartphones and the Acoustic Doppler Effect in High School

Abstract: Experiments using smartphones allow for teaching physics concepts in a fun and engaging way and including interdisciplinary approaches. The exploratory character of the experimental activities, along with the smartphones’ embedded technologies, when applied in the high school classroom, also has the potential to awake the students’ intrinsic motivation, contributing to more meaningful learning. Here, using two smartphones running free apps and a personal computer for data analysis, we present an experiment pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This issue is unavoidably neglected in the investigations involving the acoustic version of the experiment [1][2][3][4] where it could be even explicitly contradicted by highlighting symmetries between the approaching and receding phases, without specifying that they are valid only approximately and in a very limited range of velocities (for example [4] p. 567).…”
Section: Moving Source and Receiver At Rest: Measuring The Doppler Shiftmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue is unavoidably neglected in the investigations involving the acoustic version of the experiment [1][2][3][4] where it could be even explicitly contradicted by highlighting symmetries between the approaching and receding phases, without specifying that they are valid only approximately and in a very limited range of velocities (for example [4] p. 567).…”
Section: Moving Source and Receiver At Rest: Measuring The Doppler Shiftmentioning
confidence: 99%
“…The Doppler effect has always been a highly intriguing phenomenon for students and a source of teachers' inspiration for constantly renewed educational proposals. Recently, for example, the use of devices closer to students' experience (smartphones) and more powerful and versatile tools for analyzing video recordings (Tracker), has been the recurring focus of several publications devoted to the acoustic Doppler effect (see for example [1][2][3][4] and the references therein). Still in connection with the use of new technologies, starting from a work by Serra [5], other recent papers studied the Doppler shift with plane surface waves on water [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…(low pitch) when the siren moves away from the listener. Several studies reported well-designed approaches to support students' learning about the Doppler effect [3][4][5][6][7][8][9]. They integrated up-todate technologies or devices into experiments, for example, using a smartphone application as a sound generator, analysing data via the Tracker freeware, and applying a video analysis technique to a ripple tank [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The observed frequency versus time graph for a given sound frequency when the mobile phone rotates in a uniform circular motion can be interpreted using equation (4).…”
Section: Introductionmentioning
confidence: 99%
“…The experiment enables the study of wave optics by taking pictures of diffraction patterns even in a condition where ambient light is on. We also highlight some experiments designed to study the Doppler acoustic effect using smartphones acting both as a sound source and receiver [3] or only as a receiver [4]. Considering the sensibility of the measuring sensors and apps, these works achieve good results for high frequency sound waves.…”
Section: Introductionmentioning
confidence: 99%